Investigation of material flow and thermomechanical behavior during friction stir welding of an AZ31B alloy for threaded and unthreaded pin geometries using computational solid mechanics simulation - Giorjao, R. A.R. (2021)
In the friction stir welding process, the tool role in the material flow and its thermomechanical behavior is still not entirely understood. Several modeling approaches attempted to explain the material and tool relationship, but to this date, insufficient results were provided in this matter. Regarding this issue and the urgent need for trustful friction stir welding models, a computational solid mechanic's model capable of simulating material flow and defect formation is presented. This model uses an Arbitrary Lagrangian-Eulerian code comparing a threaded and unthread pin profile. The model was able to reproduce the tool's torque, temperatures, and material flow along the entire process, including the underreported downward flow effect promoted by threaded pin's. A point tracking analysis revealed that threads increase the material velocity and strain rate to almost 30% compared to unthreaded conditions, promoting a temperature increment during the process, which improved the material flow and avoided filling defects. The presented results showed the model's capability to reproduce the defects observed in real welded joints, material thermomechanical characteristics and high sensitivity to welding parameters and tool geometries. Nevertheless, the outcomes of this work contribute to essential guidelines for future friction stir welding modeling and development, tool design, and defect prediction.